GALLIUM-67 CITRATE USED AS A TRACER OF ACETONE PRODUCTION ROUTE (Brazilian Journal of Radiation Sciences (BJRS), 2019)
In this work the pathway of the chemical product and the kinetics parameters were evaluated in a laboratory plant settled, using 0.4 GBq (10 mL) of 67Ga citrate as radiotracer and 18 NaI(Tl) radiation detectors.  The AnaComp program was used to estimate the kinetic para ameters of the acetone production. The yield of the acetone production was estimated by the percentage ratio between the areas under the curve (AUC) of the curve profiles of the final product compartment divided by the concentration found inside the chemical reactor whose result was 87% yield during the first 30 minutes of reaction.